2018
DOI: 10.1038/s41591-018-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting skeletal endothelium to ameliorate bone loss

Abstract: Recent studies have identified a specialized subset of CD31hiEMCNhi vascular endothelium that positively regulates bone formation. However, it remains unclear how CD31hiEMCNhi endothelium levels are coupled to anabolic bone formation. Mice with an osteoblast-specific deletion of Shn3, which have markedly elevated bone formation, demonstrated an increase in CD31hiEMCNhi endothelium. Transcriptomic analysis identified SLIT3 as an osteoblast-derived, SHN3-regulated proangiogenic factor. Genetic deletion of Slit3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
299
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(310 citation statements)
references
References 52 publications
6
299
0
1
Order By: Relevance
“…These results complement published studies demonstrating that deletion of Slit3 in cathepsin K–expressing cells decreased bone formation rate and trabecular bone volume, although osteoclast number and eroded surface were also increased in this mouse model . Although the impact of osteoblast lineage–derived SLIT3 on the skeleton remains somewhat controversial, our data firmly support the concept that osteoclast‐derived coupling factors, including SLIT3, play an important role in skeletal homeostasis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results complement published studies demonstrating that deletion of Slit3 in cathepsin K–expressing cells decreased bone formation rate and trabecular bone volume, although osteoclast number and eroded surface were also increased in this mouse model . Although the impact of osteoblast lineage–derived SLIT3 on the skeleton remains somewhat controversial, our data firmly support the concept that osteoclast‐derived coupling factors, including SLIT3, play an important role in skeletal homeostasis.…”
Section: Discussionsupporting
confidence: 91%
“…Given that deletion of Srgap2 in the myeloid lineage caused an increase in bone formation, we considered potential clastokines that may mediate such a response. Recently, SLIT3 was identified by two different groups as an osteoclast‐derived and osteoblast‐derived bone anabolic factor that acts in a paracrine fashion . Western blot analysis confirmed that SLIT3 protein was induced in BMMs cultured in the presence of M‐CSF and RANKL; moreover, expression of SLIT3 was greater in differentiated osteoclasts from Srgap2‐cKO mice compared to control (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…The related pathophysiological changes include cancer, cardiovascular diseases, neurological diseases, metabolic syndrome, and motor system diseases . Osteoporosis is a debilitating chronic bone disease accompanied by increased bone loss and a high risk of fracture and is the most common reason for fracture among the elderly . Currently, numerous drugs have been produced to treat osteoporosis by inhibiting bone resorption, although they offer few benefits to bone formation and fail to reverse bone loss .…”
Section: Mechanisms Underlying Melatonin's Action On Osteoporosismentioning
confidence: 99%
“…These networks promote downstream osteogenetic molecules (eg, ALP, BMP2, and osteoprotegerin) and osteolysis molecules (TNF-α, ROS, IL-1β, IL-6) the most common reason for fracture among the elderly. [49][50][51][52][53][54] Currently, numerous drugs have been produced to treat osteoporosis by inhibiting bone resorption, although they offer few benefits to bone formation and fail to reverse bone loss. 55 Moreover, conventional therapies have their own adverse effects, such as osteonecrosis, 56 atrial fibrillation, 57 esophageal cancer, 58 eczema, 59 cellulitis, 60 deep venous thrombosis, 33 and osteosarcoma, 61 all of which may contribute to a lack of compliance.…”
Section: Melatonin Maintains Metabolic Homeostasis In Bonementioning
confidence: 99%
“…Recently, researchers have identified a new type of vessel, termed type H vessels, which show strong expression of CD31 and endomucin (Emcn) in the endothelium . These vessels couple the opposing processes of bone absorption and formation . Although the relative abundance of these specific vessels is low, many osteoprogenitor cells are distributed around them .…”
Section: Introductionmentioning
confidence: 99%